Study of the therapeutic effect of an alcoholic extract of (Gundelia tournefortii) on non-alcoholic fatty liver disease caused by carbon tetrachloride in albino rats and its comparison with atorvastatin - دريوس, محمد; سلامه , ريم; أسعد , يوسف (Latakia University Journal -Biological Sciences Series, 2021)
The study aimed to test the therapeutic effect of the alcoholic extract of Gundelia tournefortii leaf on non-alcoholic fatty liver disease induced in white mice and to identify some of the biochemical and histological changes associated with that. The study was conducted on 40 mice in four equal groups. The mice of the experimental groups were respectively injected as follows: The first (control) with NACL physiological solution (0.9%), The second group were injected with a single dose of ccl4 (1 ml/kg) to induce lubrication, The third group was injected with the same previous dose of ccl4 and daily doses of the alcoholic extract of the leaves of the Gundelia tournefortii plant for 10 weeks (250 mg/kg of body weight), The forth group were injected intraperitoneally only once with a dose of ccl4 and with daily doses of Atorvastatin (250 mg/kg body weight) for 10 weeks. The results of the biochemical study showed a significant increase (p<0.05) in the average values of (TG, ALT, and AST) in the second group compared with the control, and the results also showed a significant decrease (p<0.05) in the averages of the previous values in the third group and the fourth compared with the second group, as for the average sugar values the increase was significant (p<0.05) in the fourth group compared with the rest of the groups. The results of the histological study of the livers of mice of the second experimental group showed the emergence of clear lubrication, which some cases reached the point of necrosis, while the results of the livers of mice of the third and fourth groups showed a clear improvement in the hepatic cell compared with the second group, where fat was minimal and this confirms the important therapeutic role of Gundelia tournefortii extract with its active ingredients (besides Atorvastatin) against the nonalcoholic lipidosis.